2004
DOI: 10.1111/j.0300-9475.2004.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Anti‐Inflammatory Effects of Glucuronoxylomannan in Collagen‐Induced Arthritis

Abstract: This investigation was planned to assess the therapeutic efficacy of glucuronoxylomannan (GXM) in collagen-induced arthritis (CIA). GXM was isolated from culture filtrate of Cryptococcus neoformans var. gattii, serotype C. CIA was induced by the immunization of Dark Agouti rats with bovine type II collagen in incomplete Freund's adjuvant. GXM solution at two doses, 25 and 50 mg/kg, was administered intraperitoneally. Onset of i.p. injections of GXM to prevention and treatment groups was days 0 and 10 postimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is noteworthy that CAP67 vesicles induced an even higher production of TNF-␣ in comparison to HEC3393 vesicles (Fig. 3), possibly because these fractions lack GXM, which causes potent depressive effects on immune function (44,45,70,73). IL-10 and TGF-␤ levels were increased following exposure to either vesicle fraction (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…It is noteworthy that CAP67 vesicles induced an even higher production of TNF-␣ in comparison to HEC3393 vesicles (Fig. 3), possibly because these fractions lack GXM, which causes potent depressive effects on immune function (44,45,70,73). IL-10 and TGF-␤ levels were increased following exposure to either vesicle fraction (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…However, high doses of GXM (500 g/ml) are not toxic to immune cells in vitro, and these doses injected in mice do not alter hematological parameters in vivo (unpublished results). Moreover, a previous study demonstrated the high tolerability of GXM compared with some steroids such as Dex and other nonsteroidal antiinflammatory drugs (43).…”
Section: Discussionmentioning
confidence: 98%
“…The results of a variety of in vivo and in vitro studies have suggested that cryptococcal polysaccharide triggers the shedding of L-selectin from leukocytes [5][6][7][8][9][10][11][12]. L-selectin on the surfaces of leukocytes is involved in the initial binding and rolling of leukocytes, a process that precedes extravasation into infected tissues and lymph nodes [13,15,18].…”
Section: Discussionmentioning
confidence: 99%
“…component, glucuronoxylomannan (GXM), has a key role in suppressing the inflammatory recruitment of leukocytes [5][6][7][8][9][10]. HIV-infected patients with cryptococcal meningitis have ratios of GXM in serum to GXM in CSF that inversely correlate with the numbers of leukocytes in CSF [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation